Implementasi Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) dalam Meningkatkan Kemampuan Problem Solving dan Kreativitas Peserta Didik Pada Pembelajaran Matematika di SMK Negeri 2 Medan - Afifah Tamimi; Dwi Novita Sari; Haryati Ahda Nasution; Seprianti Harahap; Amalia Retno Wulandari (Journal on Education, 2024)
This research aimed to improve the problem-solving abilities and creativity of students in class XI TITL-5 at SMK Negeri 2 Medan in learning mathematics through the implementation of the Student Teams Achievement Division (STAD) cooperative learning model. The research design used was Classroom Action Research (CAR) with two cycles of action. The research subjects were 30 students of class XI TITL-5. The instruments used included problem-solving ability tests, creativity questionnaires, Lesson Plans (RPP), Student Worksheets (LKPD), and observation sheets. The results showed that the application of the STAD cooperative learning model could significantly improve students' problem-solving abilities and creativity. In cycle I, the average problem-solving ability of students was 58.78, and the average creativity was 51.33. After the actions in cycle II, the average problem-solving ability increased to 81.03, and the average creativity reached 75.16. Thus, the STAD cooperative learning model proved effective in improving the problem-solving abilities and creativity of students in class XI TITL-5 at SMK Negeri 2 Medan.